Wave stress and biotic facilitation drive community composition in a marginal hard‐bottom ecosystem. Issue 10 (1st October 2019) - Westerbom, Mats; Kraufvelin, Patrik; Erlandsson, Johan; Korpinen, Samuli; Mustonen, Olli; Díaz, Eliecer
Abstract: Ecological patterns are inherently scale‐dependent and driven by the interplay of abiotic gradients and biotic processes. Despite the fundamental importance of such gradients, there are many gaps in our understanding of how abiotic stress gradients interplay with biotic processes and how these collectively affect species distributions. Using a hierarchical design, we sampled two communities separated by depth along wave exposure and salinity gradients to elucidate how these two gradients affect species composition in habitats formed by the foundation species Mytilus trossulus and Fucus vesiculosus . Specifically, we looked at the impacts of regional salinity and temperature, local wave exposure, and site‐dependent facilitation effects on the associated community composition. Wave exposure was the best predictor for species assembly structure, which was also affected by Mytilus biomass and by salinity and water temperature. While the tested variables provided robust explanations for community structure and density, they did not provide conclusive explanations for variation in species richness or evenness. Mytilus biomass had a stronger effect on the associated community with increasing wave exposure at the deeper depth, but the patterns were less obvious at the shallower depth. The latter was also the case for Fucus . These findings comply partly with theoretical predictions suggesting stronger facilitation effects in physically harsh environments. Our results indicate that environmental drivers are the main structuring forces that affect species assembly structure, but also foundation species are important. Thus, predicting changes in species distributions and biodiversity requires the simultaneous consideration of environmental gradients, as well as the structure and composition of foundation species and the interplay between these factors. This work advances our understanding of the processes that modulate species distributions in a marginal marine area and broadens the knowledge of how biological and environmental factors interplay and have an influence on hard‐bottom community structure in brackish water seas.